Sarcoidosis-associated pulmonary hypertension - Kašiković-Lečić Svetlana; Obradović Dušanka; Sazdanić-Velikić Danica; Popović Milan; Javorac Jovan; Živanović Dejan (Association of Nurses Technicians and Midwives, 2022)
The diagnosis of sarcoidosis-associated pulmonary hypertension is a challenge, because there are signs and symptoms, such as dyspnea, dizziness, and chest pain that are nonspecific and may exist in both diseases. Right heart catheterization is the gold standard for the diagnosis of pulmonary hypertension. However, this is an invasive procedure, so it is reserved for patients with a high probability of the presence of pulmonary hypertension. Current guidelines for the diagnosis of pulmonary hypertension recommend transthoracic echocardiography for the screening method. Adequate treatment of underlying diseases and comorbidities is important in order to prevent disease progression, disability, and shortened patient survival. Specific therapy for SAPH is not routinely recommended.